2022
DOI: 10.3390/ijms24010716
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Epigenomics in the Molecular Biology of Melanoma—A Prerequisite for Biomarkers Studies

Abstract: Melanoma is a common and aggressive tumor originating from melanocytes. The increasing incidence of cutaneous melanoma in recent last decades highlights the need for predictive biomarkers studies. Melanoma development is a complex process, involving the interplay of genetic, epigenetic, and environmental factors. Genetic aberrations include BRAF, NRAS, NF1, MAP2K1/MAP2K2, KIT, GNAQ, GNA11, CDKN2A, TERT mutations, and translocations of kinases. Epigenetic alterations involve microRNAs, non-coding RNAs, histones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…Malignant transformation of melanocytes with further progression to advanced stages, collectively called melanomagenesis, is initiated and driven by environmental, genetic (inheritable), constitutional, and epigenetic factors, as well as by acquired mutations with the accumulation of genomic changes further amplified by local and systemic neuroimmunoendocrine factors affecting progression of the disease [ 1 , 2 , 4 , 6 , 9 , 11 , 12 , 13 , 14 , 30 , 32 , 50 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Since these factors have been discussed in many review articles, we will only provide a brief overview of them.…”
Section: Cutaneous Melanoma In a “Nutshell”mentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant transformation of melanocytes with further progression to advanced stages, collectively called melanomagenesis, is initiated and driven by environmental, genetic (inheritable), constitutional, and epigenetic factors, as well as by acquired mutations with the accumulation of genomic changes further amplified by local and systemic neuroimmunoendocrine factors affecting progression of the disease [ 1 , 2 , 4 , 6 , 9 , 11 , 12 , 13 , 14 , 30 , 32 , 50 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Since these factors have been discussed in many review articles, we will only provide a brief overview of them.…”
Section: Cutaneous Melanoma In a “Nutshell”mentioning
confidence: 99%
“…Malignant transformation of melanocytes and further progression to advanced stages of melanoma are driven by environmentally induced somatic mutations in a cellular, tissue, and systemic context-dependent fashion as discussed in numerous reviews [ 1 , 2 , 4 , 6 , 10 , 11 , 18 , 30 , 36 , 37 , 74 , 76 , 77 , 82 , 86 , 126 , 127 , 128 , 129 , 130 ]. Therefore, our overview on this topic will be brief.…”
Section: Cutaneous Melanoma In a “Nutshell”mentioning
confidence: 99%
“…Although malignant melanoma (MM) represents only 1–8% of the skin neoplasia, it is responsible for approximately 65–75% of the deaths through cutaneous cancer, with associated high mortality caused by its metastases, which can appear in one third of the cases [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Thereby, understanding the tumor spread mechanisms and identifying predictive factors for the metastases becomes of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…So far, at least 20 genes have been identified that play a role in melanoma pathogenesis. The most frequently mutated are BRAF, NRAS and KIT oncogenes [ 29 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%